The Door of Last Resort : Memoirs of a Nurse Practitioner - Frances Ward (Rutgers University Press, 2013)
Uninsured and underinsured urban residents receive primary care in starkly contrasting health facilities—from expensive, state-of-the-art hospital emergency departments staffed by hospitalists to neighborhood health centers staffed by nurses. In the latter, nurse practitioners use basic diagnostic tools to offer primary care services. The focus is on patient context. Here, I take my stand. Through narratives of my experiences as an adult nurse practitioner in both an urban emergency department and in rudimentary nurse-managed urban health centers, I give voice to the scope of practice of a nurse practitioner. Such stories reveal how nurse practitioners think. Beyond cognition, the stories help me describe the intricate network of relationships that exist among providers in various community-based organizations. This web of relationships sustains the financially fragile yet critically needed safety net that binds us together in the service of a common humanity. The stories offered in chapter 1 establish questions that will be explored further in other chapters: Who owns the language of health care? Is health care patient centered or provider centered? And, with their focus on the patient’s context, just how disruptive are nurse practitioners in a health care system that reimburses for the singular cost of illness?